2015
DOI: 10.1021/acs.joc.5b02172
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Synthesis of Heparan Sulfate Oligosaccharides

Abstract: Heparan sulfates are implicated in a wide range of biological processes. A major challenge in deciphering their structure and activity relationship is the synthetic difficulties to access diverse heparan sulfate oligosaccharides with well-defined sulfation patterns. In order to expedite the synthesis, a divergent synthetic strategy was developed. By integrating chemical synthesis and two types of O-sulfo transferases, seven different hexasaccharides were obtained from a single hexasaccharide precursor. This ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 69 publications
2
54
0
Order By: Relevance
“…Previous work by Zaia and coworkers have shown that amide-HILIC retention time is dominated by acetyl and sulfate composition for Hp/HS oligosaccharides of a given size 39 , indicating that FGF2 binding increases as sulfate content increases. This is consistent with previous microarray results using synthetic oligosaccharides that showed that FGF2 binds all highly sulfated GAG tetrasaccharides well, while intermediately sulfated structures showed a clear structure-function relationship 40 , and is consistent with other FGF2 binding structure-function studies showing preference for high sulfation and indicating the importance of 2- O -sulfation and N -sulfation to FGF2 binding 41-44 .…”
Section: Resultssupporting
confidence: 92%
“…Previous work by Zaia and coworkers have shown that amide-HILIC retention time is dominated by acetyl and sulfate composition for Hp/HS oligosaccharides of a given size 39 , indicating that FGF2 binding increases as sulfate content increases. This is consistent with previous microarray results using synthetic oligosaccharides that showed that FGF2 binds all highly sulfated GAG tetrasaccharides well, while intermediately sulfated structures showed a clear structure-function relationship 40 , and is consistent with other FGF2 binding structure-function studies showing preference for high sulfation and indicating the importance of 2- O -sulfation and N -sulfation to FGF2 binding 41-44 .…”
Section: Resultssupporting
confidence: 92%
“…Subsequent studies greatly expanded the repertoire of GAG oligosaccharides available in a glycoarray. For instance, the groups of Xuefei Huang and Jian Liu collaborated to synthesize several GAG oligosaccharides by assembling the GAG carbohydrate backbone using de no synthesis and then sulfating them using sulfotransferases (Figure ) . This method allowed them to create nine Hp hexasaccharides with differing sulfation patterns for microarray study.…”
Section: Microarray Technology In Gag Interactomicsmentioning
confidence: 99%
“…For instance, the groups of Xuefei Huang and Jian Liu collabo-rated to synthesize severalG AG oligosaccharidesb ya ssembling the GAG carbohydrate backboneu sing de no synthesis and then sulfating them using sulfotransferases (Figure 2). [38] This method allowed them to create nine Hp hexasaccharides with differing sulfation patterns for microarrays tudy.T he Liu group went on to create am icroarray of fourteen HS heptasaccharideu sing only chemoenzymatic synthesis in as eparate study. [24ai] In that study,t he authors also attempted toq uantify the density of oligosaccharide on the surface by digesting the immobilized oligosaccharides with Hp lyases andq uantifying the released disaccahrides.T heir conclusion was that immobilization efficiency ranged from 1t o1 0%.R ecently,t he most ex-tensiveG AG microarray created to date has just been published by Boons and colleagues.…”
Section: à[24au]mentioning
confidence: 99%
“…The chemical synthesis of H/HS oligosaccharides is challenging due to the laborious and repetitive steps of protection, uncontrolled stereoselective glycosylation, deprotection, and multiple purification processes, which give low efficiencies and low yields. 15 However, over the years, chemical and chemo-enzymatic 16 methodologies have been reported for the synthesis of heparin-like oligosaccharides, 17 20 and the heparin-based drugs fondaparinux 21 and idraparinux. 22 To overcome the disadvantages of multi-step oligosaccharide synthesis, we have developed a computer database, OptiMer, to store the relative reactivity values (RRVs) of many glycosyl donors/acceptors.…”
Section: Introductionmentioning
confidence: 99%